2003
DOI: 10.1007/s00270-003-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome after Intrahepatic Venous Stent Placement for Malignant Inferior Vena Cava Syndrome

Abstract: We evaluated the clinical outcome of malignant inferior vena cava (IVC) syndrome after intrahepatic IVC stent placement by retrospective analysis of 50 consecutive patients (25 men, 25 women, age 32-83 years) with malignant IVC syndrome who were treated with intrahepatic stent placement. Gianturco-Rosch-Z (GRZ) stents (n = 45), and Wallstents (n = 5) were inserted. Clinical outcome was assessed from patients' records using a score based on leg swelling, scrotal/vulvar edema, ascites and anasarca before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…21 Although the literature regarding stenting for malignant IVC obstruction is scarce, the available literature demonstrates promising outcomes and high technical success of 78 to 100%. 21,47,49,55 Razavi et al demonstrated a primary patency rate at 19 months of 80% and primary assisted patency rate of 87%. 56 In our institution, we usually obtain either triple phase CT (noncontrast, arterial phase and delayed phase) or CT venograms prior to IVC recanalization procedures to evaluate the length of IVC occlusion, possible involvement of the renal or hepatic veins, the presence of thrombus, and patency of veins both caudal and cephalad to the mass.…”
Section: Inferior Vena Cava Obstructionmentioning
confidence: 99%
“…21 Although the literature regarding stenting for malignant IVC obstruction is scarce, the available literature demonstrates promising outcomes and high technical success of 78 to 100%. 21,47,49,55 Razavi et al demonstrated a primary patency rate at 19 months of 80% and primary assisted patency rate of 87%. 56 In our institution, we usually obtain either triple phase CT (noncontrast, arterial phase and delayed phase) or CT venograms prior to IVC recanalization procedures to evaluate the length of IVC occlusion, possible involvement of the renal or hepatic veins, the presence of thrombus, and patency of veins both caudal and cephalad to the mass.…”
Section: Inferior Vena Cava Obstructionmentioning
confidence: 99%
“…A retrospective analysis of 50 patients with malignant IVC obstruction treated with intrahepatic stent placement noted high rates of stent patency and durable symptom palliation. 6 Additional series confirm the efficacy of endovascular treatment for malignant IVC obstruction. 7,8 Successful implantation and resolution of edema has additionally been reported in cases of IVC thrombosis.…”
Section: Letters To the Editormentioning
confidence: 86%
“…Unlike the obstruction of the SVC where primary small cell and nonsmall cell lung cancers are most often implicated, the obstruction of the IVC may be caused by a plethora of different histologies, with primary hepatocellular and metastatic colon cancer being the most frequently reported [2][3][4][5][6][7]11,12]. Patients with malignant IVC obstruction most often have advanced metastatic disease and are deemed palliative because of their poor performance status or the lack of effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy may also be unsafe in this setting where hepatic and renal function can be compromised, and the patients often have a poor performance status. Expandable, intraluminal stent placement is an option for the treatment for malignant IVC compression; however, they are usually deployed in a palliative setting with very low median overall survivals after the stents are deployed [2][3][4][5][6][7]. In this report, we describe a case of extended patient survival and patency of an IVC stent after placement of the endoprosthesis for severe compression of the IVC from a large right hepatic lobe colon cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%